Experimental Investigation on Strength Properties of Foam Concrete - Dhanalakshmi Ayyanar; JN.Puvaneshwaran; E.Vipurajan; M.Shahul Hameed; J.Jeyaseela (East Asian Journal of Multidisciplinary Research, 2023)
Today, energy is at the forefront of issues that are critical to all governments. The ever increasing global population, along with expanding industry, has resulted in an inevitable increase in energy demand. Nowadays, in order to get desired benefits while using less energy, the issue of insulation has arisen, and thus the necessity of insulation has increased. Foamed concrete has properties such as a high strength-to-weight ratio and a low density. The use of foamed concrete minimizes dead loads on the structure and foundation, aids to energy saving, and saves construction labour costs. In this study the mechanical properties of foamed concrete was analyzed and the strength prediction of compressive was determined with the help of MATLAB. Interaction terms such as cement, flyash, marble sludge powder, water and foaming agent  within a volume were inferred as a input and compressive strength is the output with training of 3 hidden layers were used to improve the efficacy of the predictive modeling of the foam concrete.